Pelatihan Pembuatan Elektrolisis Dengan Minyak Jelantah Pada Pembelajaran SMPN 4 Pasuruan Dalam Meningkatkan Kualitas Riset: Industri Kreatif - Wijaya, Dika Putra; Fitriyani, Citra Eka; Kurnia, Nur Laili Eviana Indah; Aliyatulmuna, Adilah; Zakia, Neena; Sari, Meyga Evi Ferama Sari; Danar, Danar; Putri, Nasywa Alifia Sandi; Darmawan, Fairuz Indah; Kholilah, Khusnul (LPPM Stikosa - AWS, 2023)
SMPN 4 Pasuruan is one of the public schools in Pasuruan City, this school is located in Purworejo District in Pasuruan City. More precisely located on Jalan RW. Monginsidi, No. 56, Kebonagung, Purworejo District, Pasuruan City, East Java, 67111. This service is part of the Student Service scheme in the science, technology and environment categories, through the leading areas of science and technology implementation for the management of East Java's local superior potential. This service is carried out in several stages, namely 1) Conducting socialization to students of SMPN 4 Pasuruan regarding the content and potential of local biological materials (used cooking oil) to be made biodiesel independently in producing this oil using electrolysis cells with the potential for marketing the product, 2) Conducting direct assistance to train students at SMPN 4 Pasuruan and provide used cooking oil production equipment and, 3) Report preparation. The promised outputs from this service are 1) Progress and Final Reports, 2) Publication of scientific articles/social media. The conclusion of this community service aims to provide skills and knowledge training to participants who are students and teachers of SMPN 4 Pasuruan about using used cooking oil to make entrepreneurial products. The target achieved in this program is that participants are able to know and process the main ingredient in the form of used cooking oil into more useful entrepreneurial products.